The association of Life’s Simple 7 and infertility among U.S. women - Wang, Lixia; Chang, Guangting; Cai, Shu; Zou, Xiaofang; Qin, Meijiao; Tan, Yingyao (Frontiers in Endocrinology, 2024)
Background: The Life's Simple 7 (LS7) metric is a comprehensive measure of cardiovascular health (CVH) that encompasses seven distinct risk factors and behaviors associated with cardiovascular disease (CVD). Some studies have shown an association between infertility and CVD. The present study aimed to explore the potential association between the LS7 factors and infertility.A cross-sectional study was conducted on a sample of 3537 women aged 18-44 years from the National Health and Nutrition Examination Survey (NHANES) spanning the years 2013-2018.The LS7 metrics encompassed various factors including physical activity, smoking habits, body mass index, blood pressure levels, dietary patterns, blood glucose levels, and total cholesterol levels. We computed a 14-point LS7 score based on participants' baseline data, classifying them as "inadequate"(3-6), "average" (7-10), or " ideal" (11-14). Infertility is defined as an affirmative answer to either of two questions on the NHANES questionnaire: "Have you tried to conceive for at least one year without success?" and "Have you sought medical help for your inability to conceive?" Logistic regression was utilized to estimate odds ratios (O.R.s) and 95% confidence intervals (C.I.s).In total, 17.66% of participants were classified as individuals who reported experiencing infertility. In the continuous analysis, each one-unit increase in LS7 score was associated with a significantly decreased odds of infertility (OR=0.88 [0.77-0.89]). Analyzing the categorical representation of LS7 score, compared to individuals with poor scores, those with ideal scores exhibited a substantial 58% reduction in the odds of infertility (OR=0.42 [0.26-0.69]). Additionally, the observed interaction suggested that the influence of age on the relationship between LS7 and infertility is not consistent across different age groups (P for interaction < 0.001). Among individuals aged 35 or younger, each unit increase in LS7 score was associated with a substantial 18% (OR=0.82 [0.76-0.89]) decrease in the odds of infertility. However, in the older age group (>35), the association was attenuated and non-significant.Our research suggests a significant inverse association between LS7 scores and infertility. Age demonstrated a varying impact on this relationship, with a more pronounced impact observed among individuals aged 35 or younger.